STUDY OF CEMENT BOND FAILURE DUE TO CHANGE OF TEMPERATURE IN STEAM INJECTION WELL - Sonny Irawan, Sonny (2008)
In this study, expansion experiments are conducted to demonstrate that expanding cements can prevent defective cement bond which is the formation of microannulus in steam injection well. The main concern of this well is the well exposes to the high temperature and pressure cycle throughout the life of the well. For example, high temperature steam that injected into the wellbore causing thermal expansion to the casing as if we stop injecting the steam, the wellbore temperature is decrease therefore the casing diameter will return to its original size. This phenomenon caused a gap between the cement sheath and the casing or the formation that known as microannulus. To overcome this problem,the hydration volume change and the mechanical properties of cement sheat under downhole condition were measured in the laboratory tests. These test show that cement slurry formulations can be optimized to meet the property requirements for steam injection well. Properties of different cement systems are compared and their applicability to steam injection well is discussed. Expansive additive is added in the cement slurry. As expansion occurs, the cement is restrained by the formation and by the casing so that expansion produces a self-stress in the cement. Therefore, this paper discusses the output of the expanding experiments that conclude expanding cement helps to prevent defective cement bond in steam injection well.